The occupation of Armazém da Utopia in the port area of Rio de Janeiro (Urdimento: Revista de Estudos em Artes Cênicas, 2022)
The challenge for theatrical groups concerned with socially engaged theatre is to reduce the impasses of capitalism through performing arts activities in alternative venues to ensure the exercise of citizenship. The appropriation of the industrial heritage warehouses not originally intended to be theatrical opened new possibilities for the performing arts in Rio de Janeiro, besides working at different scales and producing dramatic architectures. The interviewee is the theater director Luiz Fernando Lobo of Ensaio Aberto who proves that the occupation of this centenary and deactivated warehouse by a theater group with a long trajectory in the carioca scene is an act of resistance. Lobo gave the occupied building a social function, meaning a territory of struggle in a historic neighborhood on the outskirts of downtown, as an alternative to the logic of city marketing and the real estate market.
Keywords: Artistic occupation; Industrial heritage; Political theater